Effect of Atherosclerosis Developed from Diabetes on Ceruloplasmin Concentration, Ceruloplasmin Ferroxidase Activity and its Specific in Sera of Diabetic Iraqi Patients with Atherosclerosis - Safa Naji Jasim, Jwan Abdulmohsin Zainulabdeen, (Pakistan Journal of Medical & Health Sciences, 2022)
Atherosclerosis is one of the common complications in patients with advanced type 2 diabetes (T2DM). This study aims to detect the influence of this complication on ceruloplasmin concentration, ceruloplasmin ferroxidase activity and its specific activity. Samples were collected in the morning from males and females’ individuals (50-69years) who attended Ibn Al-Bitar center for cardiac surgery. Fasting serum glucose (F.S.G), malondialdehyde (MDA), Ceruloplasmin concentration, Ceruloplasmin ferroxidase activity and its specific activity were all measured after the participants fasted for about 8-12hours.The F.S.G, Ceruloplasmin Ferroxidase activity and its specific activity had a high significant increase at p<0.001. Meanwhile and Ceruloplasmin concentration had a significant increase at p<0.05. Keywords: Diabetes, Atherosclerosis, Ceruloplasmin, Ferroxidase.